1981
DOI: 10.1139/z81-302
|View full text |Cite
|
Sign up to set email alerts
|

Population ecology of Columbian ground squirrels in southwestern Alberta

Abstract: The characteristics of a large population of Columbian ground squirrels (Spermophilus columbianus), the numbers of which varied between ca. 700 and 1000 animals emerging in the spring, were studied over a 7-year period in southwestern Alberta. Over time, the density of nonjuvenile squirrels varied between 11.6 and 16.1/ha, with a sex ratio that consistently favoured females; the density of juveniles varied between 4.6 and 20.7/ha, but with a sex ratio that was usually balanced. Spatially, the density of squirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 22 publications
0
57
0
Order By: Relevance
“…Mating date was determined by examination of external reproductive morphology, observation of a copulatory plug, presence of sperm in vaginal smears (Murie and Harris 1982), direct observation of copulations above ground (at Turnbull), or by observations of precopulatory behavior, such as male interest in the female prior to, but not following, copulation, or males entering burrows with estrous females. Survival of young to yearling age can be ascertained because juveniles do not disperse prior to their first hibernation (Boag and Murie 1981, Murie and Harris 1984, Risch et al 1995. Thus, juveniles that emerge from their hibernaculum in the following spring are the ones that have survived their first hibernation.…”
Section: Field Methodsmentioning
confidence: 99%
“…Mating date was determined by examination of external reproductive morphology, observation of a copulatory plug, presence of sperm in vaginal smears (Murie and Harris 1982), direct observation of copulations above ground (at Turnbull), or by observations of precopulatory behavior, such as male interest in the female prior to, but not following, copulation, or males entering burrows with estrous females. Survival of young to yearling age can be ascertained because juveniles do not disperse prior to their first hibernation (Boag and Murie 1981, Murie and Harris 1984, Risch et al 1995. Thus, juveniles that emerge from their hibernaculum in the following spring are the ones that have survived their first hibernation.…”
Section: Field Methodsmentioning
confidence: 99%
“…Survival of juveniles overwinter was determined based on emergence the following spring. Columbian ground squirrels exhibit male-biased dispersal, which does not occur until after the first hibernation (Boag and Murie, 1981;Murie and Harris, 1984;Dobson and Murie, 1987). Thus, juveniles that did not emerge the following spring were assumed to have died during the hibernation period.…”
Section: Field Workmentioning
confidence: 99%
“…(1) Powell and MacIver (1977) found that a 3-10-year period was as adequate as a long-term period (>30 years) for describing the summer temperature and precipitation at sites within and adjacent to our study region, and (2) Boag and Murie (1981), Bronson (1977Bronson ( , 1979, and Murie et at. (1980) found small or nonexistent interyear differences in ground squirrel life histories during several multi-year studies.…”
mentioning
confidence: 89%
“…(1980) found small or nonexistent interyear differences in ground squirrel life histories during several multi-year studies. One of these studies spanned 7 years (see Boag and Murie, 1981;Murie et al, 1980) and concerned two populations in our study region where litter size and its variance, adult survival, and age at maturity did not significantly change among years. Notwithstanding, juvenile survival within our study region may vary among years (Boag and Murie, 1981;Murie, 1985;Murie and Harris, 1982), so we examine several measures of immature survival to help compensate for possible biases.…”
mentioning
confidence: 99%